Mediating Effects of Social Support on Caregiver Burden and Quality of Life for Compound and Noncompound Caregivers. Issue 2 (April 2021) - Marsack-Topolewski, Christina N.
This study sought to explore the mediating effect of informal social support on the relationship between caregiver burden and quality of life among compound and noncompound caregivers. Parents ( N = 320) completed a web-based survey aimed to examine effects of caring for an adult child with autism spectrum disorder. Results of the mediation analysis suggested that informal social support partially mediated the relationship between caregiver burden and quality of life for both groups. Informal social support appears to be more impactful for noncompound caregivers compared with compound caregivers based on a greater reduction in explained variance. These results highlight the importance of informal social support as caregivers juggle ongoing challenges to provide care to one or more care recipients.